2021
DOI: 10.1007/s00265-021-03101-5
|View full text |Cite
|
Sign up to set email alerts
|

Urban lizards use sleep sites that mirror the structural, thermal, and light properties of natural sites

Abstract: Global change processes such as urbanization are likely to affect sleep behavior, by altering abiotic (e.g., thermal and illumination) and biotic conditions (e.g., predation pressure) that influence sleep. However, little is known of how sleep behavior responds to urbanization and whether this response is flexible or conserved across populations. We quantified sleep site characteristics of the peninsular rock agama Psammophilus dorsalis in Bangalore city and surrounding rural areas. We find that P. dorsalis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…night (ALAN) on sleeping sites in lizards (Psammophilus dorsalis) and glow time in sexual signalling by glow worms (Lampyris noctiluca). Mohanty et al (2021) found that the sleeping sites of lizards in urban areas match the properties of those of lizards in natural sites in terms of the amount of light the lizards are exposed to and the structural and thermal traits. This creative and trail blazing study is one of the first to explore sleep behaviour, and we expect other studies to see the usefulness of exploring this question in urban areas.…”
Section: Using Behavioural Ecology To Explore Adaptive Responses To A...mentioning
confidence: 88%
“…night (ALAN) on sleeping sites in lizards (Psammophilus dorsalis) and glow time in sexual signalling by glow worms (Lampyris noctiluca). Mohanty et al (2021) found that the sleeping sites of lizards in urban areas match the properties of those of lizards in natural sites in terms of the amount of light the lizards are exposed to and the structural and thermal traits. This creative and trail blazing study is one of the first to explore sleep behaviour, and we expect other studies to see the usefulness of exploring this question in urban areas.…”
Section: Using Behavioural Ecology To Explore Adaptive Responses To A...mentioning
confidence: 88%
“…The ways in which the environmental effects of urbanization scale across space can influence the relative importance of these potential selection factors for species survival (Uchida et al, 2021). For an urban utilizer like P. dorsalis, which is known to exhibit high behavioral and physiological flexibility in response to urbanization (Amdekar et al, 2018;Batabyal and Thaker, 2019a;Mohanty et al, 2021), most features of urbanization showed little effect on its distribution and abundance. However, not all species are expected to respond as urban utilizers (Fischer et al, 2015), and studies that increase spatial and temporal resolution of sampling will be needed to understand the distribution patterns of those taxa and of biodiversity in general.…”
Section: Discussionmentioning
confidence: 99%
“…Lizards in the urban areas are also less risk averse, as measured by their shorter flight initiation distances from an approaching human (Batabyal et al, 2017), and are faster to learn the locations of safe refuges (Batabyal and Thaker, 2019a). The behavioural flexibility of this species extends to the selection of sleep sites that limit artificial illumination in urban areas (Mohanty et al, 2021). In the social and sexual context, males of P. dorsalis utilise a reactive social coping style in urban areas, unlike the proactive strategy of males in rural areas (Batabyal et al, 2017;Batabyal and Thaker, 2019b).…”
Section: Psammophilus Dorsalis In Bengalurumentioning
confidence: 99%
See 1 more Smart Citation
“…Anthropogenic habitat modification, such as urbanisation and agricultural development, substantially alters spatial attributes of landscapes. These transformative processes fragment, degrade and/or remove natural ecosystems (Alberti 2016), creating novel environments and conditions (Mohanty et al 2021), modifying resource availability and diversity (Lim et al 2017), and introducing exotic species (Arazmi et al 2022), pathogens (Mavroidi 2008) and toxic contaminants (Lettoof et al 2022). As urbanisation increases at a rate and scale unmatched by background levels of understanding functional traits of urban-adapted vertebrate species has been conducted on birds (Callaghan et al 2019;Evans et al 2011), mammals (Santini et al 2019), and amphibians (Liu et al 2021), but is broadly lacking for reptiles.…”
Section: Introductionmentioning
confidence: 99%